2019
DOI: 10.1080/13621718.2019.1687635
|View full text |Cite
|
Sign up to set email alerts
|

Residual neural network-based fully convolutional network for microstructure segmentation

Abstract: In this study, microstructures of weldment produced using carbon steel A516 grade 60 were analysed via a deep learning approach to measure the fraction of acicular ferrite which considerably influences on mechanical properties of carbon steel. The fully convolutional network was used to conduct the image segmentation. Submerged arc welding was used for welding, and the dataset was constructed using optical microscope. The model was compiled with ResNet, which is the state-of-the-art classifier used as an encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Azimi et al reported the successful implementation of VGGNet 17 , which is a pretrained CNN proposed by Krizhevsky, for classifying microstructures from LOM and SEM images of a steel 18 . Since then, a number of studies applying CNN have been conducted such as the application of DenseNet 19 to detect defects in steels 20 and ResNet18 21 to classify microstructures of welded steels 22 . It was verified that the performance of CNN-based methods is as good as that of humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azimi et al reported the successful implementation of VGGNet 17 , which is a pretrained CNN proposed by Krizhevsky, for classifying microstructures from LOM and SEM images of a steel 18 . Since then, a number of studies applying CNN have been conducted such as the application of DenseNet 19 to detect defects in steels 20 and ResNet18 21 to classify microstructures of welded steels 22 . It was verified that the performance of CNN-based methods is as good as that of humans.…”
Section: Introductionmentioning
confidence: 99%
“…2 Graduate School of Engineering, The University of Tokyo, 7-3-1 Hongo, Bunkyo, Tokyo 113-8656, Japan. * email: inoue@ material.t.u-tokyo.ac.jp www.nature.com/scientificreports/ to detect defects in steels 20 and ResNet18 21 to classify microstructures of welded steels 22 . It was verified that the performance of CNN-based methods is as good as that of humans.…”
mentioning
confidence: 99%
“…Roberts et al 18 proposed a DenseNet based U-Net model for semantic segmentation of metallographic images. Jang et al 19 proposed a ResNet-based U-Net segmentation network. Both of these approaches are well-known in the literature on semantic segmentation 12 .…”
Section: Related Workmentioning
confidence: 99%
“…For example, a type of CNN was used for segmenting the microstructures of welded carbon steel to measure the fraction of acicular ferrite. 108 A segmentation algorithm derived from U-Net 90 and DenseNet 94 was used for semantic segmentation of three common crystallographic defects in structural alloys. 109 Image segmentation is typically supervised learning where the training data are created manually via labor-intensive methods.…”
Section: Semantic Segmentationmentioning
confidence: 99%